A broadband magnetotelluric survey for Mt. Meakandake volcano with special attention to the unrest during 2016–2017 - Tomohiro Inoue; Takeshi Hashimoto; Ryo Tanaka; Yusuke Yamaya (Earth, Planets and Space, 2022)
Abstract We performed a broadband magnetotelluric (BBMT) survey and three-dimensional resistivity modeling for the Meakandake volcano in eastern Hokkaido, Japan, where remarkable ground deformation suggests a sill-like intrusion on the northeastern flank from 2016 to 2017. The volcano remained unerupted, and therefore the volcanological meaning of the deformation was unclear, making the evaluation of the “unrest” event difficult. Our 3D MT model has revealed a subvertical low-resistivity column C1 (approximately 1–10 Ωm) extending from 0.5 km BSL (below sea level) to a deeper part of Mt. Meakandake. The conductor C1 was not right on the presumed sill but just beneath the summit craters offset southwest. We performed a sensitivity test in which the bottom limit of C1 was varied, and confirmed that C1 was meaningful down to approximately 30 km BSL. The vertical reach in depth was necessary to reproduce the impedance phases out of quadrant at some sites west of Mt. Meakandake. In addition, we interpreted that the uppermost part of C1 was probably connected to the active vents of Mt. Meakandake through presumed subvertical pathways of heat and fluids, corresponding to the alignment of microearthquakes. On the other hand, we found no remarkable conductivity anomalies beneath the northeastern flank, where the sill-like inflation source was presumed. While our MT data do not suggest a thin sill at depth, it does not exclude the possibility that the ground inflation has been caused by a lateral magmatic or hydrothermal intrusion that branched from a certain depth of the subvertical conductor C1. Graphical Abstract